Enhancing TOEFL Structure Scores with TOEFL Test Pro: An Insight into Android-Based Learning - Arda Adianto; Eva Sulistiana; Lisa Septia Dewi Br. Ginting (Institut Agama Islam Negeri Palopo, 2025)
Generally, English has been taught in Indonesia for ages, yet it is still accounted as a great barrier for Indonesian people. They often faced the necessity of good English proficiency in many areas, such as school or even the workplace, proven in such a certification. TOEFL is one of the most commonly known certification providers, yet many students reported having difficulties in reaching a certain score, especially in the structure and written expression section. This is a pre-experimental study with a one-group pre-post-test design in an effort to improve structure using the TOEFL Test Pro application. The population sample of this study was 104, with 78 respondents using probability sampling under some inclusion criteria. The data collection was done by using an assessment format and an interview, which were then analyzed by using t-tests and paired t-tests. The results show that there were significant differences in the students pre- and post-test scores with a significant value of 0.000 < 0.05. Therefore, the use of TOEFL Test Pro enhances students' structure and written expression scores.